Assessment and revitalization of UiTM's Malaysia corporate image: repositioning strategy towards becoming a world class university / Prof. Madya Dr. Rosidah Musa, Dr. Lennora Putit and Jamaliah Mohd. Yusof - Musa, Rosidah; Putit, Lennora; Mohd. Yusof, Jamaliah (Research Management Institute (RMI), 2011)
This research study aims to investigate the relationship between service quality and University Teknologi MARA's (UiTM) overall corporate image, total students' experience (TSE) and emotional attachment (EA). The study generally adopts a mixed mode approach in its research design. From a total of 1000 respondents, only 726 data were usable and generated for further analysis using SPSS software 16.0 and AMOS 16.0 respectively. Significant implications can be gathered from the said findings. In essence, UiTM should emphasize more on the management of its facilities, followed by program quality being offered and subsequently, the number of student population. Other factors such as support staff and management, academic staff are also playing significant roles in developing students' perception of UiTM's image in general.